Major Lexical Changes in the Middle English and New English Periods of English Language Development (Journal of Pedagogical Inventions and Practices, 2022)
Vocabulary is the most active part of the language, which has changed with the development of the dialect and the emergence of new words. Studying the lexical changes of the two periods of development of the English language, it is possible to notice how the influence of the French language on the vocabulary of the English language occurred, as well as the process of romanization of French loanwords, the use of certain suffixes and prefixes, the assimilation of English basics, the emergence of one of the important innovations of Middle English - zero derivation, the formation of numerous hybrids because of massive borrowing.